Radiological prevalence of osteoarthritis of the cervical region in 104 performing Warmblood jumpers. (11th January 2021) - Espinosa‐Mur, Pablo; Phillips, Kathryn L.; Galuppo, Larry D.; DeRouen, Anthony; Benoit, Philippe; Anderson, Eleanor; Shaw, Karen; Puchalski, Sarah; Peters, Duncan; Kass, Philip H.; Spriet, Mathieu
Abstract: Background: Cervical osteoarthritis (OA) has been documented as a potential source of pain and poor performance in sport horses. Objectives: To assess the prevalence of cervical OA in a population of Warmblood jumpers and its correlation with age, level of performance, neck pain and mobility. Study design: Descriptive observational study. Methods: Warmblood jumpers free of lameness or neurological disorders were selected. Cervical pain and range of motion of the neck were subjectively assessed. Left to right lateral views were taken at C3‐C4, C4‐C5, C5‐C6 and C6‐C7. The presence of OA at the cervical articular process joints (APJs) was evaluated and graded as absent, mild or moderate to severe by three board‐certified radiologists. The agreement between radiologists and the potential associations between OA grades with age and other variables were statistically assessed ( P  < .05). Results: One hundred and four horses were included [median age = 10 years (range 6‐18 years)]. Agreement between radiologists varied from fair to substantial (Kappa‐weighted 0.37‐0.61). The C6‐C7 APJ was most commonly affected by OA with only 32.7% of APJ considered free of radiographic abnormalities at this location versus 60.5% at C5‐C6, 81.7% at C4‐C5 and 84.6% at C3‐C4. Horses competing in higher level classes (peak of performance) had significantly higher OA grades at C6‐C7 ( P  = .013). There was no association between age, age when started jumping, neck pain and neck range of motion with the presence of OA on radiographs. Main limitations: Open enrolment and lack of orthogonal views. Conclusions: This study showed that, although there is a range of interpretation of radiographic findings of the APJ, OA of the caudal cervical region is not rare in performing sound Warmblood jumpers. This suggests that OA in the caudal cervical region may be of low clinical significance.